If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + 6k = 14 Solving 26 + 6k = 14 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 6k = 14 + -26 Combine like terms: 26 + -26 = 0 0 + 6k = 14 + -26 6k = 14 + -26 Combine like terms: 14 + -26 = -12 6k = -12 Divide each side by '6'. k = -2 Simplifying k = -2
| 3D+8=2dminus-17 | | -0.25x+0.10y=1.05 | | =5.6 | | r+11+8r=25 | | r+11+8r=2555555555555 | | 22m+22=30 | | N(x)=-0.3x^2+9x+15 | | 1/2x-5=-17 | | 6x+2=CBD | | (20x^-3)/(2x^-5) | | log[3](x-5)+log[3](x+3)=2 | | 1/2(ln2-ln1) | | 77/s=132/48 | | -x^2+x-18= | | X/4=80 | | 0.7x=0.864 | | -4(4y-5)+3(3y+5)= | | 8/t=840/210 | | 9p=96 | | 2x^2-3x+.05=0 | | e^4=y | | 250y-y^2=10000 | | A/5=105 | | y/493=228/116 | | 664/996=r/12 | | N/2=33 | | 15n-125=175 | | 4x-3y/8z | | 1=3-d | | 28/42=y/12 | | 12/14=t/42 | | X/8=-1 |